Comparison of different positioning techniques for reduction of induced vertical deviation following Nishida procedure for the treatment of sixth nerve palsy - Chong-Bin Tsai; Chien-Liang Fang (PLoS ONE, 2025)
Purpose Induced vertical deviation is a potential complication following the Nishida procedure for the treatment of sixth nerve palsy. This study aims to compare different positioning techniques for the reduction of this complication. Methods We retrospectively examined medical records from consecutive patients who underwent the Nishida procedure, classifying them into three positioning groups: intra-quadrant (IQP), lateral rectus border (LRBP), and horizontal meridian (HMP). Surgical and pre/postoperative data were compared. Results Among the 27 included patients (8 IQP, 9 LRBP, 10 HMP), all three groups demonstrated similar reductions in esodeviation: IQP, 44.0 ± 18.7 Prism Diopters (PD); LRBP, 42.2 ± 15.3 PD; HMP, 42.2 ± 7.8 PD; (P = 0.675). After surgery, one patient in the IQP group developed hypertropia of 18 PD, necessitating a secondary surgery to treat the vertical diplopia. In the LRBP group, two patients had hypotropia of 30 PD and 10 PD, respectively, and one patient had hypertropia of 6 PD. In the HMP group, one patient initially had hypertropia of 2 PD, which resolved during subsequent follow-up. A lower incidence of induced vertical deviation was observed in the HMP (10%) and IQP (13%) groups compared to the LRBP group (33%). However, this difference did not reach statistical significance due to the small sample size. Conclusion There is no statistically significant difference among the three positioning techniques (IQP, LRBP, HMP) in the correction of esodeviation and reduction of incidence of induced vertical deviation following Nishida procedure.